Characterisation of Aluminium Metal Matrix Composites reinforced with SiC (Carborundum) & Al2O3 (Corundum). Issue 1 (October 2021) - Gangaraj,; Manjunath, K.
Abstract: Aluminium alloys are widely used in aerospace and automotive industries due to their advantages of physical and mechanical properties. This paper presents a study on the performance of stir cast SiC & Al2O3 reinforced Aluminium metal matrix composite materials. The particulate reinforcement of SiC & Al2O3 is in the ration of 3:2. The mechanical characterization of AMMC indicates that the composite exhibit improved physical and mechanical properties such as low coefficient of thermal expansion, high ultimate tensile strength, high impact strength and hardness. Through scanning electron microscope, the microstructure of AMMC & distribution of SiC & Al2O3 particles in Aluminium alloy (Al 1350) is uniform. By experimental analysis, it is observed that AMMC with 15% of particulate reinforcement of SiC & Al2O3 with a ration of 3:2 (9% of SiC & 6% of Al2O3) is the optimum mixture for AMMC to obtain better mechanical characteristics. This AMMC has good potential for the applications in automotive industry to manufacture engine components.